Performance Evaluation of the LoRa E220-900T30D for Wind Turbine Monitoring Systems: RSSI Measurements, Propagation Model Analysis, and Compliance with Indonesian Communication Regulations - Indah Kurniawati; Ridho Akbar; Reynanda Bagus Utomo; Muhammad Yustin Salsabila (Journal of Telecommunication Electronics and Control Engineering (JTECE), 2026)
Wind turbines require reliable real-time monitoring systems to ensure performance and operational safety. LoRa-based IoT technology is selected due to its long-range capability and low power consumption. This study evaluates the performance of the LoRa E220-900T30D module for wind turbine monitoring in Bangkalan by measuring RSSI at distances from 10 to 2600 m and comparing the results with the Free-Space, Two-Ray, and Okumura-Hata propagation models. The findings show that the Okumura-Hata model best matches the field conditions and is used to predict communication coverage up to 10 km. With the transmit power limited by Indonesian regulations (100 mW) and LoRa sensitivity (–124 dBm), the maximum communication distance is approximately 6.8 km. The range can be extended to about 9.5 km by increasing the Spreading Factor, though at the cost of reduced data rate. This study demonstrates the feasibility of LoRa for wind turbine monitoring in rural environments through optimized device configuration